Evidence for the formation of comet 67P/Churyumov-Gerasimenko through gravitational collapse of a bound clump of pebbles. (25th October 2017) - Blum, Jürgen; Gundlach, Bastian; Krause, Maya; Fulle, Marco; Johansen, Anders; Agarwal, Jessica; von Borstel, Ingo; Shi, Xian; Hu, Xuanyu; Bentley, Mark S; Capaccioni, Fabrizio; Colangeli, Luigi; et al.
Abstract: The processes that led to the formation of the planetary bodies in the Solar system are still not fully understood. Using the results obtained with the comprehensive suite of instruments onboard the European Space Agency's Rosetta mission, we present evidence that comet 67P/Churyumov-Gerasimenko likely formed through the gentle gravitational collapse of a bound clump of mm-sized dust aggregates ('pebbles'), intermixed with microscopic ice particles. This formation scenario leads to a cometary make-up that is simultaneously compatible with the global porosity, homogeneity, tensile strength, thermal inertia, vertical temperature profiles, sizes and porosities of emitted dust and the steep increase in water-vapour production rate with decreasing heliocentric distance, measured by the instruments onboard the Rosetta spacecraft and the Philae lander. Our findings suggest that the pebbles observed to be abundant in protoplanetary discs around young stars provide the building material for comets and other minor bodies.